Tube continued: morphogenesis of the Drosophila tracheal system - Schottenfeld, Jodi (2010)
The Drosophila respiratory organ (tracheal system) consists of epithelial tubes, the morphogenesis of which is controlled by distinct sets of signaling pathways and transcription factors. The downstream events controlling tube formation and shape are only now beginning to be identified. Here we review recent insight into the communication between neighboring tracheal cells, their interactions with the surrounding matrix, and the impact of these processes on tube morphogenesis. We focus on cell-cell interactions that drive rearrangement of cells within the epithelium and that are essential for maintenance of epithelial integrity, and also on cell-matrix interactions that play key roles in determining and maintaining the size and shape of tube lumens.